Pengembangan Ecobrick sebagai Teknologi Tepat Guna dalam Mendukung Identitas Desa Ramah Lingkungan di Desa Bapuhbandung - Adinda Berliana Eka Aprilia; Tarisa Zanja Bella; Risma Indra Febrianti; Salma Rosyidatul Islamiah; Titik Setya Nigrum; Meisya Dwi Lestari; M. Irvan Safarudin; Wahyu Tri Prambudi; Tri Winarsih (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program was conducted by Group 7 of KKN ITB Ahmad Dahlan Lamongan in Bapuhbandung Village, Glagah District, Lamongan Regency, aiming to address environmental and public health issues through the utilization of ecobricks and the cultivation of family medicinal plants (TOGA). The main problems identified were low awareness of plastic waste management and the underutilization of home yards for medicinal plants. The program applied a participatory assistance method involving students, parents, youth, and village officials throughout the stages of observation, planning, implementation, and evaluation. The results showed that more than 300 ecobricks were produced and assembled into an installation forming the word “BAPUHBANDUNG,” which now serves as a new village icon. In addition, medicinal plants such as ginger, turmeric, and lemongrass were planted around the installation area and residents’ yards. The evaluation indicated high community participation, good-quality ecobricks, and positive initial growth of TOGA. This program not only produced physical outputs but also increased community awareness of plastic waste management, family health independence, and the strengthening of village identity.